The Role of Culture in International Peace-Keeping and Business Operations - Orphanides, Andreas G. (IJRDO - Journal of Social Science and Humanities Research, 2019)
This paper presents and analyzes the effects that the multiplicity and diversity of cultures have on the smooth and normal operation of multinational peace-keeping forces or of international firms in a foreign country, and makes relevant recommendations.